The Geographic and Affective Territories of Comédias do Minho and Teatro do Vestido - Coelho, Rui Pina (2019)
With one of their most visible work priorities being the examination of how to relate their artistic undertakings with the fabric of the surrounding community, both Teatro do Vestido and Comédias do Minho propose two very different ways of understanding the subject as they employ territory and memory as determining components of their work. Although the course of the two groups’ individual histories (TdV, founded in 2001; CdM, founded in 2003) is testament to the rather distinct ways they have established themselves artistically in the community, their work with specific communities – from a specific geographical, professional or social context – is a recurrent theme which attracts both collectives. The Comédias do Minho maintain a more “traditional” relationship with the community. Founded in 2003, their goal is to provide the region with its own cultural entity, one focusing upon three areas of action: a theatre company, an educational project, and a community project. The Teatro do Vestido, from Lisbon, was founded by a team from multi-disciplinary backgrounds with the ambition to produce both their own dramatic texts and all the elements required for the performances, and although their recurrent theatrical practice is inscribed upon the territory, their inclination is more clearly one of a singular relationship with memory and archival documents. Within the context of extreme precariousness of those in the theatre, the erosion of the notion of the public sphere, theatre collectives’ diminishing capacity for intervention and with growing ignorance of history, collectives such as Comédias do Minho and Teatro do Vestido, in radically different ways, have built bridges with the City, fighting against the corrosion of memory, of the sense of belonging, and of community.